Multifocal tuberculosis: Many faces of an old menace - Liaqat Ali Chaudhry (International Journal of Mycobacteriology, 2013)
Tuberculosis continues to be a major health problem, and is among the leading causes of morbidity and mortality worldwide. Pulmonary tuberculosis is the commonest and epidemiologically the most important type of tuberculosis as the source of spread in the community. Some patients presenting with pulmonary tuberculosis also have associated multifocal extra-pulmonary tuberculosis and vice versa. Among these patients, some have predisposing factors for the development of disseminated tuberculosis, such as a heavy Mycobacterial load, weak or impaired innate or acquired immunity owing to diabetes, immune therapies, substance abuse or AIDS. Multifocal tuberculosis is characterized by the presence of large multifocal tuberculosis areas in the same or different adjacent or distant organs. This study presents a series of 20 patients with multifocal tuberculosis. Materials and methods: The patients' records were reviewed to locate those with multifocal tuberculosis as well as pulmonary tuberculosis during the period between 4/2003 and 12/2010. A total of 1,388 patients with confirmed open pulmonary tuberculosis were admitted at the tuberculosis center within the Dammam Medical Complex. Out of this group of patients, 20 cases (1.5%) were found to have multifocal tuberculosis. Conclusion: Multifocal tuberculosis is observed both in immunocompetent as well as in those with weak or compromised immune systems. A thorough physical examination is required even in those confirmed pulmonary cases of tuberculosis to suspect and find extra-pulmonary involvement, because it is important from the management and prognostic perspective. The ultimate outcome under DOTS (directly observed treatment short course) was good in the majority of these cases, and only a few of them required surgical intervention.